PENGARUH TRANSPARANSI LAPORAN KEUANGAN, PENGELOLAAN ZAKAT, DAN SIKAP PENGELOLA TERHADAP TINGKAT KEPERCAYAAN MUZAKKI - Nasim, Arim; Syahri Romdhon, Muhammad Rizqi (Program Studi Akuntansi FPEB UPI, 2014)
The purpose of this study was to determine how the effect of transparency of financial reporting, management of zakat, and the manager attitudes towards the level of trust muzakki. (Case studies on amil zakat institutions in Bandung).This study includes research into the associative casual. Sampling technique used was non-probability sampling using Quota sampling technique. The data used are primary data using a questionnaire research instruments. In analyzing the data, researchers used statistical regression analysis that had previously been tested with test instruments and classical assumption.The results of this study indicate that; First there is a significant influence on the level of transparency of financial statements muzakki trust. Secondly, there is a significant influence on the level of confidence in the management of zakat muzakki. Thirdly there is a significant influence on the level of trust managers attitude muzakki. Fourth, the existence of significant influence transparency of financial reporting, management of zakat, and the attitude of managers simultaneously on muzakki confidence level.Â